You Never Give Me Your Money? : Sovereign Debt Crises, Collective Action Problems, and IMF Lending - Committeri, Marco; Spadafora, Francesco (Washington, D.C. : International Monetary Fund, 2013)
We review the impact of the global financial crisis, and its spillovers into the sovereign sector of the euro area, on the international 'rules of the game' for dealing with sovereign debt crises. These rules rest on two main pillars. The most important is the IMF's lending framework (policies, financing facilities, and financial resources), which is designed to support macroeconomic adjustment packages based on the key notion of public debt sustainability. The complementary pillar is represented by such contractual provisions as Collective Action Clauses (CACs) in sovereign bonds, which aim to facilitate coordination among private creditors in order to contain the costs of a debt default or restructuring. We analyze the most significant changes (and their consequences) prompted by the recent crises to the Fund's lending framework, not only in terms of additional financial resources, new financing facilities (including precautionary ones), and cooperation with euro-area institutions, but also as regards the criteria governing exceptional access to the Fund's financial resources. We highlight a crucial innovation to these criteria, namely that, for the first time, they now explicitly take account of the risk of international systemic spillovers. Finally, we discuss how the recent crises have provided new political support for a broader dissemination of CACs in euro-area sovereign bonds. Importantly, in the first case involving an advanced economy, CACs were activated in the debt exchange undertaken by Greece in Spring 2012.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet